(3GddHGH aj JgPjH GdEfSGfs - (3Ydj Hf eMeO Hf YHO GdcQje Hf YHO GdhGMO GdTjHGfqj GdLRQj, CHh GdMSf YR GdOjf GHf GdCKjQ , J (B630 (3g`s; (3YHO GdcQje Hf eMeO Hf efUhQ GdJejej GdSeYGfj GdeQhRj, CHh SYO,J (B562 (3g` s
(3ChdgG (B:s
(3MQa GdTjf GdeYLeI HGH GdTjf hGdCda GdTGHLfi HaJM GdTjf GdeYLeI hSchf GdCda s
(3BNQgG (B:s
(3HGH GdjGA hGdjGA GdHjYKi HaJM GdjG GdChdi hSchf GdjGA GdKGfjI BNQ GdcJGH hGdMeO ddg s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B55 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B4s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3GdJGQjNs